Pengaruh Biochar dan Residunya serta Umur Defoliasi Daun Jagung terhadap Keuntungan Hasil Jagung dan Beberapa Jenis Kacang Tipe Tegak Secara Salome di Lahan Kering - Syprianus Ceunfin; Eduardus Yosef Neonbeni; Jefrianus Nino; Yakobus P. E. S. Agu; Magdalena Sunarty Pareira; Maximus J. Seran; Valeria Metkono; Maria Y. Biamnasi (Fakultas Pertanian, Universitas Timor, 2020)
The island of Timor with a dry tropical climate causes the emergence of a variety of local wisdom as a form of adaptation to environmental conditions. In West Timor, farmers use local knowledge as part of their ancestral heritage in the traditional farming system to improve the food security of family households. One form of local wisdom is a land and crop management system in which several types of food plants are planted simultaneously at the same planting hole (Salome). This study aims to prove the presence of biochar effects and residues as well as the age of defoliation on the results of corn in intercrops of Salome with several types of beans in dry land and to obtain suitable types of bean plants that are intercropped in Salome with corn. This research was conducted in July 2018 until July 2019 in the experimental garden of the Faculty of Agriculture, Timor University, Sasi village, Kefamenanu City District, TTU Regency. This research was conducted in two stages of planting, namely stage I, namely: planting in July to November 2018. Phase II was planting carried out in November 2018 to March 2019. This study used a 2 x 3 x 3 factorial randomized block design with 3 replications + corn monoculture and bean monoculture. The first factor is the use of biochar which consists of 2 levels, namely without biochar and the use of Biochar. The second factor is the age of corn dawn defoliation consisting of 3 levels, namely without defoliation, defoliation age 35 days after planting, defoliation age is 75 HST. The third factor is the type of upright type local beans consisting of 3 levels, namely: Vigna radiata L., Vigna umbellata L., Phaseolus vulgaris L., so there are 18 combinations. The results of the first phase of the research showed that the highest seed weight of corn produced a combination of treatment without biochar with defoliation age of 35 hst corn leaves in the monoculture system while in intercropping system produced by combination of biochar treatment, the defoliation age of 35 hst of corn leaves in the type of Vigna radiata L., The results of the second phase of the study showed that the combined treatment of using biochar residue, the defoliation age of 75 hst corn leaves produced the highest weight of corn seeds which were planted with intercropping system with mung bean types. The results of the first phase of the research showed that the highest seed weight of the bean plant was produced by a combination of treatments without biochar with type bean Phaseolus vulgaris L. in the monoculture system, whereas the intercropping system was produced by a combination of the use of biochar treatment without defoliation of corn leaves with the type of Phaseolus vulgaris L. beans, The results of the second phase of the study showed that the combination of the treatment of use without biochar residue, the age of defoliation of 35 HST corn leaves with the highest type of green beans in the intercropping system. Corn yield in the Salome intercropping system at the beginning of the use of biochar has decreased compared to control but has increased again when using biochar residue, the defoliation age of 35 hst corn leaves is better than without defoliation, all types of beans are suitable for planting with the Salome intercropping system. The types of Vigna radiata L. and Vigna umbellata L. are more suitable to be planted with the Salome intercropping system with corn at the beginning of biochar and pasa use when using biochar residues.